Encapsulation of the elderberry fruit anthocyanins by spray drying - M. O. Kostenko; V. I. Deineka; L. A. Deineka (Тонкие химические технологии)
Spray-dried forms of anthocyanins were prepared in a maltodextrin matrix. The anthocyanins were extracted by maceration of elderberry fruits in 0.1 M HCl followed by extract filtration through a paper filter. The extract was partially purified by solid phase extraction in a column filled with styrene-divinylbenzene copolymer beads (Sepabeads SP859/L) or in syringe cartridges with C18 silica (BioChemMack ST, Moscow, RF) followed by re-extraction with aqueous HCl and alcohol mixtures. The procedure of reversed-phase HPLC determination of the extracted anthocyanin type is discussed in comparison to HILIC method in DIOL silica columns. The latter method was shown to be preferable to avoid systematic errors in the anthocyanin type determination. Solidphase extraction in syringe cartridges gave samples with very high anthocyanins concentration (up to 70 g of cyanidin-3-glucoside chloride equivalent). When using the copolymer sorbent, the concentration was somewhat lower: up to 27 g/l. After spray drying red powder samples with anthocyanins content more than 2% were prepared, although freeze drying gave only dark resin. The red color of the samples indicates the space separation of flavylium ions in the solid state by radicals of the maltodextrin background.